Genome-wide analysis of the CBF gene family and their transcriptional response to cold stress in Hibiscus mutabilis - Shiye Sang; Yuqiao Zhou; Yiqiong Liu (Scientific Reports)
Abstract C-Repeat Binding Factors (CBFs) are crucial in plant responses to low-temperature stress via the ICE-CBF-COR cascade, but research on these genes in woody and flowering trees remains limited. Hibiscus mutabilis, a woody flowering plant of ornamental and ecological significance, faces low-temperature stress that substantially affects its growth and distribution. Understanding its cold tolerance mechanisms can enhance its utilization and provide insights into plant adaptability to climate change-induced agricultural challenges. This study presents the first genome-wide identification and characterization of the CBF gene family in H. mutabilis. Nine HmCBFs were identified, exhibiting uneven chromosomal distribution and clustering into five phylogenetic clades. Cis-regulatory element analysis indicated potential involvement of HmCBFs in abiotic stress responses and hormone signaling. Homology analysis indicated gene duplication during evolution and a close phylogenetic relationship between H. mutabilis and kenaf. Expression profiling demonstrated higher HmCBF expression in roots than in leaves under normal growth conditions, with significantly increased expression levels at 0 and − 5 °C compared to 5 °C following cold treatment. Our screening of HmCBFs in response to low-temperatures offers valuable insights for breeding cold-tolerant H. mutabilis and contributes to a broader understanding of stress tolerance mechanisms in woody species.